Hippo pathway in cell–cell communication: emerging roles in development and regeneration - Akihiro Nita; Toshiro Moroishi (Inflammation and Regeneration, 2024)
Abstract The Hippo pathway is a central regulator of tissue growth that has been widely studied in mammalian organ development, regeneration, and cancer biology. Although previous studies have convincingly revealed its cell-autonomous functions in controlling cell fate, such as cell proliferation, survival, and differentiation, accumulating evidence in recent years has revealed its non-cell-autonomous functions. This pathway regulates cell–cell communication through direct interactions, soluble factors, extracellular vesicles, and the extracellular matrix, providing a range of options for controlling diverse biological processes. Consequently, the Hippo pathway not only dictates the fate of individual cells but also triggers multicellular responses involving both tissue-resident cells and infiltrating immune cells. Here, we have highlighted the recent understanding of the molecular mechanisms by which the Hippo pathway controls cell–cell communication and discuss its importance in tissue homeostasis, especially in development and regeneration.